Integrated School Teachers’ Experiences on Implementing Inclusive Education Policy of Nepal - Shrestha, Madhav; Neupane, Nam Raj; Giri, Ramchandra (Educational Journal, 2023)
This study entitled “Integrated School Teachers’ Experiences on Implementing Inclusive Education Policy of Nepal” was carried out to investigate the experiences of integrated school teachers in implementing inclusive education policy of Nepal. The study had been carried out by selecting ten integrated schools of Kathmandu valley by convenience sampling method. Ten special education teachers and ten physical education teachers from each schools were selected by purposive sampling method. Semi-structured interview schedule was prepared and administered to the participants through telephonic interview. The interview questions were reviewed by a physical education and special education experts to maintain its reliability. The study found that teachers have been experiencing low self-awareness about educating students with disabilities. They also experienced serious lacking in their knowledge and skill in them and also their perceptions towards inclusion was immature. They want their school administration to be more responsible and active in developing inclusive culture inside the school and also urged to provide them the opportunities of their professional development through training and exposures.